INTELLECTUAL AND METACOGNITIVE ABILITIES AS A CONDITION FOR PREVENTING THE TEACHER'S EMOTIONAL BURNING (Pedagogy of Higher and Secondary Education, 2022)
This article deals with the analysis of the peculiarities of the emotional burn-out in the pedagogic activity. The results of the empiric research on the connection between emotional burn-out with the intellectual and metacognitive abilities of a pedagogic are presented
Keywords: emotional burnout of the teacher; prevention of emotional burnout of the teacher; metacognitive abilities; psychological well-being